Re-Examining the Financial Structure and Health Nexus in Asian Economies - Xu, Yanling; Tao, Ran; Mahmood, Chaudhry Kashif; Altuntaş, Mehmet (Frontiers in Public Health, 2022)
The study's main purpose is to estimate the impact of financial structure on the healthcare sector of the Asian economies from 2000 to 2019. For empirical estimation, we have relied on 2SLS and GMM estimation techniques. Two different proxies, infant mortality and life expectancy, are used in the analysis to represent the health status of the people. The findings of both 2SLS and GMM models confirm that improved financial structure causes life expectancy to rise and infant mortality to fall. Moreover, the increased usage of the internet also exerts positive impact health status of Asian people. Further, the rise in GDP and health expenditures also improve the health status of Asian nations by increasing their life expectancy and reducing their infant mortality rate. Improvement in financial structure causes the health status of the people to rise. Therefore, to achieve superior health status development of financial structure should be part and parcel of health policies and strategies in Asian economies.